Metabolomics in hypertrophic cardiomyopathy and other myocardial diseases - Pal, N (2015)
Despite the clinical importance of hypertrophic cardiomyopathy (HCM) and a recognition that aberrant energetics contributes to its pathogenesis, significant uncertainty remains regarding the determinants of the clinical phenotype. The central hypothesis underlying this thesis is that the clinical manifestations of HCM are causatively influenced by perturbations in cellular metabolism, and that the metabolome in HCM, both at rest and during stress, is distinct from that of healthy hearts and other cardiac diseases manifesting left ventricular hypertrophy (LVH). Aortic stenosis, the most common valvular heart disease in the western world, and often presenting with a prominent phenotype of LVH, was the principal comparator disease state. The metabolome of coronary sinus effluent from densely phenotyped patients with HCM, aortic stenosis with LVH and controls was systematically studied. These patients were assessed under different physiological states (at rest and during stress induced by pacing). The present work focused on fatty acid, carbohydrate and amino acid metabolism. The metabolomic changes identified were then validated by metabolomic and an orthogonal transcriptomic analysis of genes regulating these metabolic pathways in separately recruited patient cohorts. Most prominently, this study identified substantial metabolic dysregulation in aortic stenosis, consisting of impaired fatty acid β-oxidation at rest and a trend towards reduced uptake of citric acid cycle intermediates and branched chain amino acids (BCAAs) during chronotropic stress (pacing). Transcriptomic analysis revealed only partial and ineffective upregulation in PPARA expression, with a corresponding downregulation of several PPARα target genes regulating fatty acid metabolism. In contrast, there was a seemingly appropriate upregulation of citric acid cycle activity and BCAA metabolism in HCM patients during stress. During discovery and validation stages selected metabolites differentiated the control vs aortic stenosis and HCM vs aortic stenosis cohorts with relatively similar and high area under the curve (AUC) values on receiver operating characteristic (ROC) analysis. This work presented in this thesis represents the first comprehensive analysis of changes in metabolic pathways (transcriptional to metabolome) in aortic stenosis, and its comparison to HCM. The findings represent a significant increase in our understanding of the underlying metabolic derangements accompanying these disorders and provide us with promising avenues into potential therapeutic targets (e.g. PPARα), with strong clinical translation potential.